Effects of nutrients enrichements on primary production in the Ria Formosa Coastal Lagoon (Southern Portugal) - Loureiro, Sofia (2012)
Small-scale, short-term enrichment experiments were conducted in the Ria Formosa coastal lagoon (southern Portugal), to assess the effects of nutrient availability on primary productivity, biomass (as chlorophyll a), and algal composition. Samples were collected from natural communities at three different sites in the western lagoon: Barra, oceanic inlet; Ramalhete, adjacent to a urban waste water treatment plant; and Ponte, an upstream channel used for recreation and bivalve farming. These samples were enriched separately with nitrogen and phosphorous during the extreme neap tides of the summer solstice at both high (HW) and low water (LW). The experiment was repeated during the autumnal equinox to test for seasonality, and during the following summer solstice to test for replication. The addition of nitrogen consistently stimulated the productivity and biomass during summer experiments at the two sites within the lagoon, identifying N as the most likely primary ‘‘potentially limiting nutrient’’ in the western part of the lagoon for this period. No stimulation of biomass and productivity occurred in September at the same two sites indicating the importance of other factors such as light, sedimentation or grazing pressure, as controlling the pelagic community. However, these outcomes were reversed at the oceanic inlet (Barra-HW) where there was no stimulation by nitrogen during the summer months, but there was in September, suggesting that there is a different nutritional requirement for the coastal community in comparison with the lagoon community. In samples where productivity was stimulated, diatoms were the group mostsensitive to enrichment.